Apathy in Frontotemporal Degeneration: Neuroanatomical Evidence of Impaired Goal-directed Behavior - Massimo, Lauren; Powers, John P.; Evans, Lois K.; McMillan, Corey T.; Rascovsky, Katya; Eslinger, Paul; Ersek, Mary; Irwin, David J.; Grossman, Murray (Frontiers in Human Neuroscience, 2015)
Background: Apathy, the major manifestation of impaired goal-directed behavior (GDB), is the most common neuropsychiatric syndrome associated with behavioral variant frontotemporal degeneration (bvFTD). The behavioral and biological mechanisms of apathy, however, are not well understood. We hypothesized that GDB has multiple components – including at least initiation, planning and motivation – and that GDB is supported by a network of multiple frontal brain regions. In this study, we examined this hypothesis by evaluating the selective breakdown of GDB in bvFTD, and relating these deficits to grey matter (GM) atrophy and white matter (WM) integrity. Methods: Eighteen apathetic bvFTD participants and 17 healthy controls completed the Philadelphia Apathy Computerized Test (PACT). This test quantifies each of three components of GDB hypothesized to contribute to apathy. We then used regression analyses to relate PACT scores to GM atrophy and reduced white matter (WM) fractional anisotropy (FA) in bvFTD. Results: Compared to controls, bvFTD participants demonstrated significant impairments in each of the three hypothesized components of GDB that contribute to apathy. Regression analyses related each component to disease in specific GM structures and associated WM tracts. Poor initiation thus was related to GM atrophy in anterior cingulate and reduced FA in the cingulum. Planning impairment was related to GM atrophy in dorsolateral prefrontal cortex and reduced FA in superior longitudinal fasciculus. Poor motivation was related to GM atrophy in orbitofrontal cortex and reduced FA in uncinate fasciculus. Conclusions: bvFTD patients have difficulty with initiation, planning and motivation components of GDB. These findings are consistent with the hypotheses that GDB encompasses at least three processes, that these are supported by a large-scale neural network within specific portions of the frontal lobe, and that degradation of any one of these prefrontal regions in bvFTD may contribute to apathy.